SISTEM INFORMASI MANAJEMEN DISTRIBUSI GAS 3KG BERBASIS WEB DAN ANDROID YANG TERINTEGRASI (STUDI KASUS : PT. TRITRA PERKASA BOYOLALI) - Hamdani Nindya Prasasti; Yuli Astuti (Jurnal Maklumatika, 2017)
In developing this information management system, the research conducted at PT. TRITRA PERKASA Boyolali engaged in pertamina gas distribution agent on a small scale until a large scale. Technology exists to be able to make business processes more effective and efficient, in this case the demand for gas distribution, amounting in much need of recording and reporting of data quickly to the effectiveness of labor time and cost efficiency. In this study focuses on the record of gas distribution, schedule-making, allocation from SPBE, purchasing data in accordance with the schedule allocation, and spending of the company that was once the recording is still done manually, so it often goes wrong and a long time in making the report. The output of this system is to produce data accurate managerial reports in order to supervise the performance of the company and facilitate owners in the reporting of data distribution to Pertamina. The author will use qualitative research methods, which will be made observations on the business processes running in the company as well as an interview of both the owners and staff. The author will discuss in detail about how the design and analysis of the application to be made using platforms php and android, starting from the stage of needs analysis, feasibility analysis system design, interface design, the design of the program design, design database design, implementation phase, up to the stage of testing app to be the right application to suit company needs.